The Effectiveness of Sipandem Aplication in Monitoring Adherence of Diabetes Mellitus in Kramatwatu Public Health Centre - Ernawati Ernawati; Dwi Agung Riyanto; Febri Febri (Universitas Malahayati, 2026)
ABSTRACT Diabetes mellitus is a degenerative disease that occurs due to metabolic disorders caused by problems in insulin production. Adherence is defined as an attitude and behavior aimed at fulfilling instructions or requests from others. The “SIPANDEM” application was developed to support diabetes self-management. The determine the effectiveness of SIPANDEM Aplication in monitoring adherence of Diabetes Mellitus patients. This study employed a quantitative research design with a descriptive correlational approach to examine the relationship between two or more variables using a cross-sectional method, with pairet t-test analysis. The paired t-test analysis demonstrated a statistically significant effect of the SIPANDEM application on patient adherence (p-value = 0.000). The SIPANDEM Aplication is effective in monitoring the adherence of diabetes mellitus patients Keywords: SIPANDEM, Aplication, Diabetes Mellitus, Adherence, Self-Management.